Effectiveness of Indonesian Islamic Philanthropy E-payment: A Netnographic Study - Ma'ruf, Aminudin; Mellinia, Rashifahunnisa' (AFEBI Islamic Finance and Economic Review, 2023)
The best achievement of zakat institutions in fulfilling their duties as an organization is strongly influenced by several strategies for utilizing the latest technology. Electronic payment (e-payment) plays an important role in accelerating any institutional transaction. As we all know, there are various electronic payment systems that facilitate online buying and selling transactions. This study aims to determine the effectiveness of zakat payment services through the Cinta Zakat application owned by the National Amil Zakat Agency (BAZNAS), this study uses a netnography method to analyze application user reviews through the Google Play store platform. Netnography is used to understand social interaction in the context of contemporary digital communication. The results of this study showed an analysis based on 69 user reviews of the Cinta Zakat application, including analysis of positive reviews, negative reviews, then comparison of reviews for effectiveness analysis. The percentage of 26.09% of positive reviews was shown by the aspect of ease of zakat payments through the application that users disclosed. Meanwhile, as many as 1.45% of the negative reviews were indicated by the aspects of login problems and OTP error codes. The paper is hoped to become one of the references in the field of information technology and measuring the performance of zakat workers institutions, through social media interactions.